2018
DOI: 10.1002/aur.1936
|View full text |Cite
|
Sign up to set email alerts
|

Goal prediction in 2‐year‐old children with and without autism spectrum disorder: An eye‐tracking study

Abstract: The current study examines the ability to generate visual predictions regarding other people's goal-directed actions, specifically reaching and grasping an object, in infants and children with and without autism spectrum disorder. Results showed no differences in abilities when movement information about a person's goal was evident; however, differences were evident across age and clinical diagnoses when relying on previous knowledge to generate a visual prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Although prevention science, developmental science, and neuroscience have largely proceeded along disparate lines, compelling evidence of the effectiveness of this approach will be derived via alteration of adverse neurodevelopmental trajectories towards adaptive brain:behavior patterns and healthy functioning. This must capitalize on advances in developmentally-sensitive neuroimaging and assessment that provide the capacity to detect neurodevelopmental impacts of intervention and psychopathology biomarkers from very early in life (Graham et al, 2015;Krogh-Jespersen, Kaldy, Valadez, Carter, & Woodward, 2018). Intermediate mechanisms that may explain this link would include reduced rate of escalation of irritability and impairment, and improvements in self-regulation, including executive function supported by optimal functioning of prefrontal regions (e.g., more typical recruitment of neural resources during frustration) (Grabell et al, 2017).…”
Section: Large-scale Selective Mental Health Risk Preventionmentioning
confidence: 99%
“…Although prevention science, developmental science, and neuroscience have largely proceeded along disparate lines, compelling evidence of the effectiveness of this approach will be derived via alteration of adverse neurodevelopmental trajectories towards adaptive brain:behavior patterns and healthy functioning. This must capitalize on advances in developmentally-sensitive neuroimaging and assessment that provide the capacity to detect neurodevelopmental impacts of intervention and psychopathology biomarkers from very early in life (Graham et al, 2015;Krogh-Jespersen, Kaldy, Valadez, Carter, & Woodward, 2018). Intermediate mechanisms that may explain this link would include reduced rate of escalation of irritability and impairment, and improvements in self-regulation, including executive function supported by optimal functioning of prefrontal regions (e.g., more typical recruitment of neural resources during frustration) (Grabell et al, 2017).…”
Section: Large-scale Selective Mental Health Risk Preventionmentioning
confidence: 99%
“…Researchers have asked whether the social communication impairments characteristic of children with ASD may in part be attributed to differences in their action predictions and in how they segment events (Krogh-Jespersen, Kaldy, Valadez, Carter, & Woodward, 2018;von Hofsten, Uhlig, Adell, & Kochukhova, 2009;Zalla et al, 2013). One study found that when watching a video of two adults in a typical turn-taking conversation, preschoolers with ASD (mean age of 4.7 years) made fewer predictive saccades from one speaker to the next compared to typically developing (TD) 3-year-old children (von Hofsten et al, 2009).…”
Section: Non-normative Event Prediction and Segmentation In Childrementioning
confidence: 99%
“…Research has also examined why children with ASD struggle with making predictions in agentive action. Krogh‐Jespersen et al () adapted the paradigm developed by Woodward () to assess the action prediction capabilities of children with ASD. Children were familiarized with a video of an actor reaching for and grasping one of two objects presented side‐by‐side; then, the location of the toys was flipped, and the actor raised her hand to initiate another reaching action but paused prior to making a selection.…”
Section: Significance Of Event Segmentation For Other Developmental Pmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some studies have found that ASC individuals have varying degrees of impairment in intelligence (Spencer et al, 2007), cognitive control (Solomon et al, 2008), implicit learning (Vivanti and Rogers, 2014), and action anticipation (Ganglmayer et al, 2019). Meanwhile, the impairment of intelligence, cognitive control, implicit learning, and action anticipation in ASC individuals can provide some explanation for their impairment in social communication (Lieberman, 2000; Hughes, 2001; Sinha et al, 2014; Foti et al, 2015; Krogh-Jespersen et al, 2018; Bertollo and Yerys, 2019). However, because the reports on these variables in the study of ASC individuals' empathy impairment are incomplete and the measurement tools are inconsistent, we do not further analyse these variables in this research.…”
Section: Introductionmentioning
confidence: 99%